A successful double valve repair on an interesting background: Case report - Dina Fa Alwaheidi (14779501) (2023)
Aortic regurgitation in a bicuspid aortic valve is a complex entity that involves not only the semilunar valve but also the structure of the aortic root which is functionally and pathologically in a very close relationship to it. Considering repairing a bicuspid valve mandates a mindful involvement of all related structures concurrently. Here, we report an interesting case of both bicuspid aortic valve and mitral valve regurgitation in a patient with a history of infective endocarditis, that was successfully managed by double valve repair. Other Information Published in: Journal of Cardiac Surgery License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1111/jocs.16582